Antihyperalgesic and anti-allodynic properties of cardamonin in mice model of neuropathic pain - Sambasevam, Yogesvari (2018)
Neuropathic pain is a chronic pain state caused by injury in the nervous system and often characterised by symptoms such as spontaneous pain, allodynia and hyperalgesia. Neuropathic pain is debilitating and highly resistant to current treatments such as nonsteroidal anti-inflammatory drugs (NSAIDS), anticonvulsants, antidepressants and opioids analgesics. Cardamonin is a naturally occurring chalcone. Studies have shown that cardamonin exhibited promising therapeutic effects such as antinociceptive and anti-inflammatory. Importantly, cardamonin is able to reduce the production of inflammatory mediators that are also involved in the pathophysiology of neuropathic pain. The study was aimed to investigate the antihyperalgesic and anti-allodynic properties of cardamonin in CCI-induced neuropathic pain in mice and its possible mechanism of actions. Male ICR mice were used throughout the project. CCI-induced neuropathic pain model was performed. A small incision was made to expose the sciatic nerve on the left hind leg and loose ligatures were placed around the nerve. The neuropathic pain response was measured quantitatively by using Hargreaves Plantar test, dynamic plantar aesthesiometer test, cold plate test and Randall-Selitto test. Ligations study consisted of 5 groups of animals; sham-operated, 1-Ligation, 2-Ligations, 3- Ligations and 4-Ligations. Behavioural assessments were carried out for 12 weeks. Investigation of antihyperalgesic and anti-allodynic properties of cardamonin were carried out by treating animals exposed to CCI with vehicle (DMSO, Tween20, & distilled water), Amitriptyline (20 mg/kg) or cardamonin (3, 10 & 30 mg/kg) via intraperitoneal route. All treatments were administered for 7 days consecutively from day 15 till day 21 after surgery. Behavioural assessments were carried out on day 0, 14 (before treatment & after treatment) and 21. Mechanisms of actions (MOA) that were investigated in this project were the involvement of opioid receptors, L-arginine-nitric oxide/cGMP/ATP-sensitive K+ channel pathway and potassium channels. Animals exposed with CCI were pre-treated with antagonists before the administration of cardamonin or vehicle. Behavioural tests were conducted after the administration of their respective treatments. Brain samples were collected to study the expression of opioid receptors via Western blotting. All data were collected and expressed as mean ± SEM and were statistically analysed by using one-way Analysis of Variance (ANOVA), followed by Tukey‘s post-hoc test. The results were considered significant at p<0.05. Cardamonin (3, 10 & 30 mg/kg) exhibited antihyperalgesic and anti-allodynic activities on CCI-induced neuropathic pain model in mice. Cardamonin elicited its analgesic effects by activating L-arginine/cGMP/K+-ATP channel pathway, opening the potassium channels as well as modulating pain signal via activation of delta- and kappaopioid receptors. Modulation by these pathways and ion channels suppressed the neuronal hyperexcitability that arised due to peripheral nerve injury, hence producing analgesic effects. Taken together, cardamonin has the potential to be developed as a drug candidate for management of pain.